2020
DOI: 10.1186/s12957-020-01948-y
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict skip metastasis in papillary thyroid cancer

Abstract: Background: Skip metastases are defined as lateral lymph node metastasis (LNM) without the involvement of central LNM in papillary thyroid cancer (PTC), and it is difficult to predict in clinical practice. Our study aimed to investigate the risk factors of skip metastasis and establish a nomogram for predicting the probability of skip metastasis in PTC patients. Patients and methods: A total of 378 consecutive PTC patients with clinically suspected LNM who underwent modified radical neck dissection (MRND) from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Not all PTC lesions are the same, and the lesion characteristics should be evaluated to determine which options are available for each patient [ 28 ]. Therefore, shared decision-making (SDM) should be recommended for clinical practice, which is an approach of care that involves the clinician using the best available evidence to discuss the attributes of different treatment options with patients to choose a method that makes intellectual and practical sense [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not all PTC lesions are the same, and the lesion characteristics should be evaluated to determine which options are available for each patient [ 28 ]. Therefore, shared decision-making (SDM) should be recommended for clinical practice, which is an approach of care that involves the clinician using the best available evidence to discuss the attributes of different treatment options with patients to choose a method that makes intellectual and practical sense [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…All FNA performers received certification and support from the cytology and ultrasound technician. The final FNA results were verified by at least one experienced cytopathologist (21). Nodules smaller than 10 mm in size would receive US-guided FNA when at least one of the following requirements was met: Nodular location was close to thyroid capsule, trachea, or nerve; Patients had a family history of thyroid cancer or a history of radiotherapy; Enlargement of neck LN was observed by US or neck LN was suspicious of cancer metastasis.…”
Section: Fna Technique and Categorizationmentioning
confidence: 99%
“…The nomogram is a useful and popular visual graph that illustrates the probability of occurrence of predicted events so as to guide clinical treatments [12][13][14]. Several past studies have reported that nomogram has good risk-prediction ability for post-surgical survival prognostication in patients with malignant tumors [15,16].…”
Section: Introductionmentioning
confidence: 99%